Determinants of demand for insurance in Malaysia / Noorhatikah Nasir - Nasir, Noorhatikah (2014)
This study is to investigate the determinants of demand for insurance by using data from public listed companies at Bursa Malaysia. The financial data have been tested in this study in determining the demand for insurance in Malaysia. The variables considered are tax considerations, income, savings, leverage and also growth opportunities. The sample of this study comprises of 32 observations of the independent and dependent variables on a yearly basis over 32 years period from 1980 to 2011. The data can be found from DataStream and world data bank. Interactive software package, E-views will be used for regression analyzing the data that have been collected. The variables basically from the previous research paper that related to the determinants of demand for insurance. The results of this research would determine which financial data variables have significant affect towards insurance in Malaysia.